Effects of Teachers as Coaches for Paraprofessionals Implementing Functional Communication Training. (April 2022) - Gregori, Emily; Rispoli, Mandy J.; Lory, Catharine; Kim, So Yeon; David, Marie
Young children with intensive behavioral needs are often served by paraprofessionals, who are typically among the least trained and least supported staff in the school. While professional development opportunities to address challenging behavior are generally limited for special education teachers, such professional growth opportunities are often completely unavailable for paraprofessionals. The purpose of this study was to evaluate a program in which teachers served as coaches for paraprofessionals. Using a multiple-baseline design across paraprofessional-and-child dyads, we evaluated the effects of the teachers-as-coaches program on paraprofessional implementation fidelity and child engagement in challenging behavior and appropriate communication. The results showed that with teacher coaching, paraprofessionals increased their behavior intervention implementation fidelity to 100%. During the maintenance probes, two of the paraprofessionals implemented the intervention with 100% fidelity, and the third paraprofessional implemented the intervention with higher fidelity than baseline. Results also showed corresponding decreases in child challenging behavior and increases in appropriate communication. Implications for research and practice in supporting paraprofessionals are discussed.